(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to describe the current situation of care for patients with soft tissue abscesses and to identify several related factors. Method: A cross-sectional descriptive study was conducted on 229 abscess patients treated at the Department of Orthopedic Trauma Surgery, Viet Tiep Friendship Hospital from March 1, 2025 to August 30, 2025. Results: The results showed that the majority of patients diagnosed and treated for abscesses were aged 60 years or older (42.9%). The leading cause of abscesses was infection (55.9%). Factors such as diabetes, obesity, and burns were associated with medical and surgical care with p < 0.05. Conclusion: Diabetes mellitus, as well as a history of burns or trauma, were found to be associated with the quality and process of abscess care.